The Influence of Satisfaction and Trust on Sympathy Card Customer Loyalty in Students of the Faculty of Economics and Business UPN Veteran East Java - Ardianta, Armanda; Purwanto, Sugeng (PT FORMOSA CENDEKIA GLOBAL, 2024)
Business competition in the development of the current era of globalization makes companies have to quickly think hard about how to behave and act effectively and efficiently, especially when facing competition in a business environment that moves very fast and keeps up with the times and is full of uncertainty. Therefore, every company is required to compete competitively in terms of creating and maintaining loyal customers. This study aims to analyze customer loyalty by looking at the effect of satisfaction and trust whether it can influence customer loyalty sympathy on students of the Faculty of Economics and Business UPN